2019
DOI: 10.3390/ijfs7020027
|View full text |Cite
|
Sign up to set email alerts
|

Testing Market Efficiency with Nonlinear Methods: Evidence from Borsa Istanbul

Abstract: Market efficiency has been analyzed through many studies using different linear methods. However, studies on financial econometrics reveal that financial time series exhibit nonlinear patterns because of various reasons. This paper examines market efficiency at Borsa Istanbul using a smooth transition autoregressive (STAR) type nonlinear model. I develop nonlinear ARCH and STAR models, a linear AR model and random walk model for 10 years' weekly data and then out-of-sample forecast next 12 weeks' return. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Apart from Brazil, Russia, India, China, and South Africa as BRICS countries, the efficiency of the Turkish stock market, Borsa Istanbul, has been frequently analyzed individually and also within the emerging market segment. Most recently, Aliyev (2019) examined the efficiency of Borsa Istanbul by using a smooth transition autoregressive (STAR)-type nonlinear model, nonlinear ARCH and STAR models, and two linear models, which were the linear AR model and random walk model. He examined 10 years of weekly data and then, out-of-sample, forecast the next 12 weeks' return.…”
Section: The Results Of Unit Root Testsmentioning
confidence: 99%
“…Apart from Brazil, Russia, India, China, and South Africa as BRICS countries, the efficiency of the Turkish stock market, Borsa Istanbul, has been frequently analyzed individually and also within the emerging market segment. Most recently, Aliyev (2019) examined the efficiency of Borsa Istanbul by using a smooth transition autoregressive (STAR)-type nonlinear model, nonlinear ARCH and STAR models, and two linear models, which were the linear AR model and random walk model. He examined 10 years of weekly data and then, out-of-sample, forecast the next 12 weeks' return.…”
Section: The Results Of Unit Root Testsmentioning
confidence: 99%
“…Since financial series exhibit nonlinear structures Aliyev (2019), we look at some studies that focus on nonlinear dynamics. Mahalik et al (2017) reported a non-linear inverted U-shaped association between FinDev and EnCon for the period of 1971-2011 using cointegration test and ARDL model in Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Standard GARCH models assume that positive and negative error terms have a symmetric effect on the volatility. However, financial time series in practice exhibit asymmetrical nonlinear patterns because of various reasons such as transaction costs, market frictions, arbitrage limits and others (Aliyev (2019)). This means that the impact of "bad news" or negative shocks on conditional volatility may persist longer than impact of "good news" or positive shocks.…”
Section: The Exponential Garch Modelmentioning
confidence: 99%